Field measurements at a road embankment during a winter season in northern Sweden - Motamedi, Zahra; Tommik, Karina; Mattsson, Hans; Laue, Jan; Knutsson, Sven (Transportation Geotechnics, 2025)
Understanding the thermal regime of road embankments in cold climates during winter is essential for efficient road design and accurate estimation of maintenance frequencies to reduce freeze-induced damage. In response to the challenging climate conditions in northern Sweden, an experimental field setup was designed to assess the thermal impact of culverts and accumulated snow in ditches on the thermal regime of road embankments during a winter season. This study provides detailed information on the experimental setup, highlights potential challenges from installation phase to data acquisition, and addresses measurement errors. Methods to ensure accuracy and obtain reliable data are also presented. Additionally, some of the obtained measurement results are included in this paper. The results show that snow impacts the thermal regime of the embankment from the onset of accumulation in the ditch, when the snow cover is still thin, until it reaches a depth of 65 cm. Beyond this depth, the soil beneath the snow remains almost unfrozen throughout the winter season. Additionally, the temperature distribution measurements within the embankment indicate that freezing progresses faster near the culvert compared to the rest of the embankment. However, once the culvert ends are insulated by snow cover, the frost depth in the soil near the culvert does not increase significantly, while the rest of the road continues to freeze gradually to greater depths throughout the winter season. The measurement results presented in this study provide researchers with a reliable dataset for validating numerical models in related research areas simulating cold-climate conditions. Additionally, these results enhance the understanding of the thermal regime of road embankments in typical cold climates and offer valuable insights for planning road maintenance and construction in such regions. Furthermore, this study provides essential information for researchers aiming to design and optimize experimental measurement setups in similar ...